2013
DOI: 10.1093/intimm/dxs158
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 amplifier activation in epithelial regions of bronchi after allogeneic lung transplantation

Abstract: The IL-6 amplifier, a positive feedback loop for NFκB signaling, which was originally found to be activated by IL-17A and IL-6 stimulation in non-immune cells, is molecularly a simultaneous activator of NFκB and signal transducer and activator of transcription 3 (STAT3), functionally a local chemokine inducer and pathologically a machinery for inflammation development. It has been shown that IL-6 amplifier activation in epithelial cells contributes to rejection responses in a mouse chronic rejection model that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 8 publications
0
41
0
Order By: Relevance
“…that the IL-6 amplifier, which acts as a chemokine inducer in nonimmune cells, simultaneously activated NFjB and signal transducer and activator of transcription 3 to induce cytokines, such as IL-6, and locally attracted various immune cells [44][45][46]. Recently, the involvement of EREG in the potentiation of the IL-6 amplifier was reported [19].…”
Section: Discussionmentioning
confidence: 99%
“…that the IL-6 amplifier, which acts as a chemokine inducer in nonimmune cells, simultaneously activated NFjB and signal transducer and activator of transcription 3 to induce cytokines, such as IL-6, and locally attracted various immune cells [44][45][46]. Recently, the involvement of EREG in the potentiation of the IL-6 amplifier was reported [19].…”
Section: Discussionmentioning
confidence: 99%
“…1A; ref. 2). The inflammation amplifier, which is a chemokine inducer in type I collagen þ nonimmune cells, including endothelial cells, fibroblasts, glia cells, and epithelial cells, is activated by the simultaneous activation of NF-kB and STAT and locally infiltrates various immune cells (2)(3)(4)(5). In fact, the inflammation amplifier is activated by various soluble molecules, including IL-17, TNF-a, ErbB1 ligands, and norepinephrine, which act as NF-kB stimulators, and IL-6 and IFN-g, which act as STAT stimulators ( Fig.…”
Section: Background and Summary Of Key Findingsmentioning
confidence: 99%
“…The main functional molecules of the inflammation amplifier are chemokines and growth factors, which deregulate local homeostasis via an accumulation of various immune cells and proliferate various regional cells, whereas IL-6 mainly acts as fuel to maintain the activation of STAT3 (16,17). We have shown that the amplifier is activated in the affected tissues of several disease models and clinical samples (17)(18)(19) and that its blockade suppressed these models (17,19). Furthermore, we performed genome-wide screenings of the amplifier machinery, identified .1000 positive regulators, including BCR, and .500 targets of the inflammation amplifier, all of which carried significantly high numbers of inflammatory disease-associated genes (17).…”
Section: B Reakpoint Cluster Region (Bcr) Protein Is a Unique Kinasementioning
confidence: 96%
“…We previously reported an inflammation-inducing mechanism, called the inflammation amplifier, in nonimmune cells such as synovial cells and endothelial cells (15), which is activated by a simultaneous stimulation of NF-kB and STAT3 and involved in the pathogenesis of several inflammatory disease models (17)(18)(19). By genome-wide screenings, we have identified that BCR is one of the positive regulators of the inflammation amplifier (17).…”
Section: Bcr Is Critical For Nf-kb Activation In Vivo and In Vitromentioning
confidence: 99%